MR.AGAIN (Monitoring, Report and Accumulate of Green AccountINg): Sistem Pengolahan Informasi Masyarakat Berbasis Responsive Web Design di Kabupaten Pasuruan - Warga Baroka Sugiarto; Muhammad Korib Hamdani; Tri Budi Prasetyo (Jurnal Akuntansi dan Audit Syariah (JAAiS), 2022)
Every company must be interacted with Enviroment both the case on usage of nature resource and also the location to do activities operationally. More the intense of the company's industry activities 'caused the possibilities to Enviroment damage uprising either. The company's awareness act toward the Enviroment could be shown by green accounting. The background of this essay concern for enviromental pollution of the companies in Pasuruan district. The writer's solutions that offer in the case to resolved it is MR. AGAIN (Monitoring, Report and Accumulate of Green Accounting) as a bridge to social's complain about the enviromental pollution such a waste disposal of companies.it later to be analyzed in report of green accounting. Some features become operation system's website to push the advance of the company. MR. AGAIN as a role on this essay using the Analitical descriptive method by study of information and experience by collecting data. The result of the essay in 2020 concern of society complaint about Enviroment pollution in certain district uprised. So that, the exist of MR.AGAIN that based of Responsive Web design as real act of adjustment from rapid development of technology hope able to be solutions of problems above.